Analysis of the Effectiveness of Professional Development Programs, School Committee Participation, and Government Support on Teacher Performance in East Java - Yana Priyana; Vini Rizqi; Nanny Mayasari (Westscience Press, 2024)
This study examines the influence of government support, professional development programs, and school committee participation on teacher performance in East Java, Indonesia. Using a quantitative approach, data were collected from 230 teachers and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that government support has the strongest positive effect on teacher performance, followed by professional development programs and school committee participation. Together, these factors explain 57.7% of the variance in teacher performance. The findings highlight the importance of comprehensive strategies to improve teacher performance, emphasizing the need for strong government policies, continuous professional development, and active community involvement. The study provides valuable insights for policymakers and educational leaders seeking to enhance the quality of education through improved teacher performance.